2013
DOI: 10.1016/j.ab.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of neutral human milk oligosaccharides by graphitic carbon high-performance liquid chromatography with tandem mass spectrometry

Abstract: Defining the biologic roles of human milk oligosaccharides (HMOS) requires an efficient, simple, reliable, and robust analytical method for simultaneous quantification of oligosaccharide profiles from multiple samples. The HMOS fraction of milk is a complex mixture of polar, highly branched, isomeric structures that contain no intrinsic facile chromophore, making their resolution and quantification challenging. A liquid chromatography-mass spectrometry (LC-MS) method was devised to resolve and quantify 11 majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 48 publications
7
83
3
4
Order By: Relevance
“…A method using graphite carbon HPLC- MS indicated that milk oligosaccharides differ between lactating mothers and also vary during the lactating period. 82 An LC-MS/MS method was used to investigate and quantify glycosaminoglycans in the urine of patients with MPS I, II, and VI. 83 …”
Section: Quantificationmentioning
confidence: 99%
“…A method using graphite carbon HPLC- MS indicated that milk oligosaccharides differ between lactating mothers and also vary during the lactating period. 82 An LC-MS/MS method was used to investigate and quantify glycosaminoglycans in the urine of patients with MPS I, II, and VI. 83 …”
Section: Quantificationmentioning
confidence: 99%
“…Oligosaccharides were quantified by an LC-MS consisting of a capillary HPLC (1100 Series LC, Agilent) controlled by ChemStation software (Agilent) [33]. Chromatographic resolution was on a stationary phase of porous graphitic carbon (100 × 2.1 mm, 3-µm particle size, Hypercarb, Thermo Fisher Scientific) at ambient temperature with a mobile phase of 10 % acetonitrile (Optima, Thermo Fisher) in 90 of 0.02 % (v/v) acetic acid in Milli-Q deionized water with a flow rate of 0.5 mL/min and a 5-min run time.…”
Section: Analysis Of Oligosaccharidesmentioning
confidence: 99%
“…Three classes of oligosaccharides can be distinguished in human milk: neutral fucosylated (including 2′fucosyllactose, 2′FL), neutral nonfucosylated (including lacto-N-neotetraose, LNnT), and acidic (including 3′sialyllactose, 3′SL, and 6′sialyllactose, 6′SL) (35). In contrast, cow's milk contains relatively low oligosaccharide content with limited structural diversity (6).…”
mentioning
confidence: 99%